2016
DOI: 10.5468/ogs.2016.59.6.434
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical presentation and pregnancy outcomes in antepartum preeclampsia and new-onset postpartum preeclampsia: Are these the same disorder?

Abstract: ObjectiveNew-onset postpartum preeclampsia is a poorly defined condition that accounts for a significant percentage of eclampsia cases. It is unclear whether new-onset postpartum preeclampsia is a different disorder from or belongs to the same spectrum of classic antepartum preeclampsia. The objective of this study was to compare the clinical presentation and pregnancy outcomes of antepartum preeclampsia and new-onset postpartum preeclampsia.MethodsA retrospective study including 92 patients with antepartum pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
8
0
3
Order By: Relevance
“…NOPPE and PPE are collectively termed postpartum PE. While some have reported that the prevalence of NOPPE ranges from 0.3 to 27.5% in the US 3 , 4 , another US study reported postpartum hypertension to be 63.2% 5 whereas in an African setting of Burkina Faso a prevalence of less than 2% was reported 6 .…”
Section: Introductionmentioning
confidence: 97%
“…NOPPE and PPE are collectively termed postpartum PE. While some have reported that the prevalence of NOPPE ranges from 0.3 to 27.5% in the US 3 , 4 , another US study reported postpartum hypertension to be 63.2% 5 whereas in an African setting of Burkina Faso a prevalence of less than 2% was reported 6 .…”
Section: Introductionmentioning
confidence: 97%
“…Only two prior studies have compared cases of late postpartum and antepartum preeclampsia; one found no difference in risk factors. (13) However, Vilchez (2016) found that women with late postpartum preeclampsia were significantly older, had higher gravity and parity, and were more likely to have public health insurance than those with antepartum preeclampsia, but found no difference in maternal race, body mass index, or mode of delivery. ( 14) These differences may be due to the inclusion of a comparison group with no preeclampsia or underlying differences in the populations.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, Vilchez et al found that women with late PPPE were significantly older, had higher gravity and parity, and were more likely to have public health insurance than those with APE but found no difference in maternal race, body mass index, or mode of delivery. 14 These differences may be due to the inclusion of a comparison group with no PE or underlying differences in the populations. In an alternate approach, McLaren et al fit a predictive model for PPPE readmissions, including both patients with antepartum diagnoses and incident late postpartum diagnoses, identifying race/ethnicity, blood pressure at discharge, and PE diagnosis as the predictive of readmission with a Distinct Risk Factors for Antepartum and Postpartum Preeclampsia Picon et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus study conducted on 194 patients with eclampsia (92 antepartum and 92 postpartum) showed, that patients with postpartum preeclampsia were older, multiparous and of lower socio-economic status than patients with antepartum preeclampsia, additionally, patients with postpartum preeclampsia have more clinical symptoms like headache, elevated blood pressure, abnormal vision, nausea/vomiting, seizures, shortness of breath and pedal edema, they also show significantly higher laboratory markers, than patients with antepartum preeclampsia. And additionally, they more often require blood pressure treatment after discharge [34] .…”
Section: Clinical Characteristicsmentioning
confidence: 99%